Filial piety and parental responsibility: an interpretive phenomenological study of family caregiving for a person with mental illness among Korean immigrants - Park Mijung (BMC, 2012)
Abstract Background Despite the strong influence of culture on family involvement in disease management, few studies have examined how immigrant families care for persons with mental illness. The purpose of this study was to examine how immigrant families organize their world to care for a mentally ill person in the United States. The current analysis focused on how Confucian notions of filial piety and parental obligation shape caregiving in Korean immigrant families. Methods Participants in this interpretive phenomenological study were comprised of six Korean immigrant women caring for a family member with mental illness. Participants provided narratives that illustrate challenges and opportunities in caring for their mentally ill family member. Results Three family caregiving patterns were discerned. Insulating from the outside world describes a family's effort to accept a member's illness and to manage it within the family. Prioritizing education over well-being concerns parental commitment to the Confucian priority of educating one's children. Reciprocating the sacrifice describes how a family adapts and enacts filial piety. Conclusion The findings of this study warrant further study to examine the influence of Confucianism among Korean American families. The three patterns of caregiving are strongly aligned with Confucian notion of family and family engagement. These patterns may help health providers to anticipate the needs of and provide individualized, culturally appropriate mental health care for patients with mental illness and their families of Korean origin.